1995
DOI: 10.1021/np50126a023
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antiplatelet Naphthalene from Rhamnus nakaharai

Abstract: A new naphthalene derivative, isotorachrysone [1], was isolated from the stem bark of Rhamnus nakaharai along with several known compounds. The antiplatelet effects of isotorachrysone [1], isotorachrysone peracetate [2], 6-methoxysorigenin [3], quercetin 3-O-methyl ether [4], and quercetin 3-O-methyl ether peracetate [5] were studied using washed rabbit platelets. Of the compounds tested, 1, 2, 4, and 5 showed potent antiplatelet effects on arachidonic acid (AA-) and collagen-induced platelet aggregation. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…The IC 50 values of ayanin (3) and QPME (5) were similar to that of quercetin (1), suggesting that substitution of neither the C-3, -7, and -4′ nor of the C-3, -5, -7, -3′, and -4′ hydroxyl groups with methoxy groups significantly altered the effect on PDE3 inhibition. Interestingly, the IC 50 values of QPA (6) and QMTA (7) were significantly lower than that of quercetin (1), suggesting that substitution of all the hydroxyl groups of quercetin (1) or 3-MQ (2) with acetyl groups increased the effect on PDE3 inhibition when compared to that of quercetin (1).…”
Section: Inhibitory Effects Of Quercetin Derivatives On Pde3mentioning
confidence: 96%
See 1 more Smart Citation
“…The IC 50 values of ayanin (3) and QPME (5) were similar to that of quercetin (1), suggesting that substitution of neither the C-3, -7, and -4′ nor of the C-3, -5, -7, -3′, and -4′ hydroxyl groups with methoxy groups significantly altered the effect on PDE3 inhibition. Interestingly, the IC 50 values of QPA (6) and QMTA (7) were significantly lower than that of quercetin (1), suggesting that substitution of all the hydroxyl groups of quercetin (1) or 3-MQ (2) with acetyl groups increased the effect on PDE3 inhibition when compared to that of quercetin (1).…”
Section: Inhibitory Effects Of Quercetin Derivatives On Pde3mentioning
confidence: 96%
“…In our laboratory, quercetin-3-O-methylether (3-MQ, 2) was isolated from Rhamnus nakaharai Hayata [7]. However, quercetin-3,7,4′-O-trimethylether (ayanin, 3) and quercetin-3,7,3′,4′-O-tetramethylether (QTME, 4) were synthesized according to the method described by Gomm and Nierenstein [8], and quercetin-3,5,7,3′,4′-O-pentamethylether (QPME, 5) was synthesized according to the method described by Kupchan and Bauerschmidt [9].…”
Section: Reagents and Drugsmentioning
confidence: 99%
“…8,9,18,19) To date, bioactivities of 6-methoxysorigenin and its derivatives remain largely unknown. This is the first report on their antioxidant activities.…”
Section: Resultsmentioning
confidence: 99%
“…6) It was also demonstrated a selective and competitive inhibitor of phosphosdiesterase subtype 3/subtype 4. 5) Isotorachrysone (1), an acetonaphthone isolated from R. nakaharai, showed antioxidant 7) and platelet aggregation inhibitory 8) activities. 6-Methoxysorigenin (2), isolated from the wood of R. nakaharai, possesses a structure closely analogous to 1 ( Fig.…”
mentioning
confidence: 99%
“…1) was isolated from Rhamnus nakaharai Hayata (Lin et al, 1995), and identified by spectral methods, including UV, IR, MS, and NMR spectroscopic techniques. The purity of 3-MQ was 99%.…”
Section: Reagents and Drugsmentioning
confidence: 99%